2012
DOI: 10.4103/0973-6247.95047
|View full text |Cite
|
Sign up to set email alerts
|

Family/friend donors are not true voluntary donors

Abstract: Background:Family/replacement donors still provide more than 45% of the blood collected in India. National AIDS Control Organization passed the guideline that family/friend donors should be considered as voluntary donors by the blood banks in India.Materials and Methods:We did a prospective analysis of Transfusion Transmitted Infections (TTI′s) on our family donors for the years 2009 and 2010 to compare the results and evaluate if family donors are as safe as voluntary donors.Result:The prevalence of Human Imm… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(24 citation statements)
references
References 8 publications
1
23
0
Order By: Relevance
“…Some studies have shown that family replacement donors are not true voluntary blood donors since they donate under family influence and in some cases, are hired commercial blood donors who pretend to be family members or relatives. Hence, they may not disclose relevant medical information such as previous history of jaundice or multiple unprotected sexual exposures [26]. The implication of this is that false medical information will be obtained from such donors and this may ultimately compromise the safety of the entire blood collection process.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that family replacement donors are not true voluntary blood donors since they donate under family influence and in some cases, are hired commercial blood donors who pretend to be family members or relatives. Hence, they may not disclose relevant medical information such as previous history of jaundice or multiple unprotected sexual exposures [26]. The implication of this is that false medical information will be obtained from such donors and this may ultimately compromise the safety of the entire blood collection process.…”
Section: Discussionmentioning
confidence: 99%
“…This is comparable to the observations of Sinha SK et al, 10 1.37% by Jain R, Gupta G (2012). 11 The prevalence of HBsAg either higher or lower observed may depend on actual prevalence of HBV infection in general population, repetition of the initial seroreactive samples and technical errors causing high or low absorbance value.…”
Section: Discussionmentioning
confidence: 99%
“…Lebanon has much relied on replacement donations; however, replacement donors cannot be considered as VNRD . Indeed, replacement donors are often placed under some form of coercion to give blood for their sick relatives and some do not return for a second donation until someone in their environment is in need, meaning that they are not converted to VNRD .…”
Section: Replacement Donations and Mentalitymentioning
confidence: 99%
“…They usually tend to arrive to the HBB in groups, accompanied by family members to donate blood to save the life of a given sick relative of theirs; such gesture is believed to avoid displeasing families or friends. Hence, they may conceal some information about their health or lifestyle behaviors just so that they can effectively donate, while VNRD would not hide important information relative to their own health or to infectious risks for recipients of their donated blood . Indeed, such behavior can adversely affect their own health, increase the risk of transfusion‐transmitted infections, and create additional financial burden on the HBB because any infected BC has nevertheless a cost for processing, testing, and destruction .…”
Section: Replacement Donations and Mentalitymentioning
confidence: 99%